Learning Environment, Students’ Attitude and Performance in Quantitative Course Units: A Focus on Business Students - Semukono, Freddie; ., Alice Arinaitwe (Journal of Education and Vocational Research, 2013)
This study examines the persistent poor performance in quantitative course units amongst undergraduate business students, using the case of Makerere University Business School. The data were collected from 346 third year students using a face-to-face administered questionnaire survey; and analysed using descriptive statistics, correlation and hierarchical regression analyses. The findings indicate that while learning environment and students’ attitude are positively associated with performance in quantitative courses, students’ attitude towards quantitative courses causes more variations in performance. Paucity of studies on performance in quantitative business courses deprived the study of the opportunity to cross validate the findings. Future studies should be conducted to confirm the results. Management of universities should consider learning environment and students’ attitude when determining possible changes to enhance students’ performance in quantitative courses. This study extends the predominantly mathematics studies to other business quantitative courses at university level.